2022
DOI: 10.1093/icvts/ivac237
|View full text |Cite
|
Sign up to set email alerts
|

Drainless thoracoscopic surgery should be avoided in primary spontaneous pneumothorax with pleural adhesion

Abstract: Objective Drainless thoracoscopic surgery, defined by omitting chest drain after surgery, has been demonstrated to be feasible in selected patients for pulmonary resection. However, drainless procedure for the treatment of primary spontaneous pneumothorax has raised concerns for its safety and thus has been less often reported. We aimed to share our preliminary experience regarding how to select patients with spontaneous pneumothorax for this procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, Holbek et al reported the rate of pneumothorax as 59% in their study, including 51 cases; none of the patients needed tube thoracostomy [16]. lin et al stated that pneumothorax requiring tube thoracostomy was correlated with pleural adhesion in their series including 34 cases [17]. In our study, pneumothorax was detected in 2 patients in the drainless group, and it decreased and completely resolved in follow-up radiographs.…”
Section: A B C Dmentioning
confidence: 42%
See 1 more Smart Citation
“…However, Holbek et al reported the rate of pneumothorax as 59% in their study, including 51 cases; none of the patients needed tube thoracostomy [16]. lin et al stated that pneumothorax requiring tube thoracostomy was correlated with pleural adhesion in their series including 34 cases [17]. In our study, pneumothorax was detected in 2 patients in the drainless group, and it decreased and completely resolved in follow-up radiographs.…”
Section: A B C Dmentioning
confidence: 42%
“…Lin et al . stated that pneumothorax requiring tube thoracostomy was correlated with pleural adhesion in their series including 34 cases [ 17 ]. In our study, pneumothorax was detected in 2 patients in the drainless group, and it decreased and completely resolved in follow-up radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…However, for cases with clinical pneumothorax, at least one of the three parameters exceeded the respective IQRs ( Table 4 ). Careful patient selection reduces postoperative morbidity ( 22 ). Nevertheless, due to the exploratory nature of this study, the determination of an explicit cutoff to predict postoperative morbidity was not possible, but our findings suggest that using a combination of drainage parameters rather than the flow rate alone may have a better ability to identify patients with elevated risk.…”
Section: Discussionmentioning
confidence: 99%